An Analysis of the Method of Problem Solving By SIS through a Model of Qur’anic Hermeneutics from an Islamic Thought Perspective - Kamaruddin, Zuraidah; Wan Ali, Wan Zailan Kamaruddin (Afkar: Jurnal Akidah dan Pemikiran Islam, 2013)
Sisters In Islam (SIS) is a Non-Governmental Organisation (NGO). This organisation offers alternative solutions to the problems that they claim arises in Muslim society by applying their own methods of problem solving. The founding members of Sisters In Islam (SIS) set out to find the solutions to the problems that they claim Muslim women face due to inequality practice. Thus, SIS began their work by first studying the issues faced by Muslim women and by understanding the Qur’an. A model of Qur’anic hermeneutics is one of the methods of problem solving applied by SIS. Since the method of problem solving in Islam is significant to ensure the given solution does not contradict with Islamic thought perspective, this article attempts to analyse SIS’s method of problem solving through a model of Qur’anic hermeneutics from an Islamic thought perspective. This article will benefit the Muslims because it will analyse whether a model of Qur’anic hermeneutics used by SIS can be accepted or rejected within the Islamic context.